DESIGN OF A WEB-BASED PATIENT ADMINISTRATION INFORMATION SYSTEM AT THE ATHA PERDAGANGAN CLINIC - Andina Andina (Smart Education, 2025)
Abstract : This study aims to design and build a web-based Patient Administration Information System at the ATHA Perdagangan Clinic to improve the effectiveness and efficiency of patient administration services. This system was developed to replace the manual processes currently used, such as patient registration, drug data management, room data management, and recording inpatient and outpatient payment transactions, which are prone to errors and time-consuming. The system development method includes needs analysis, system design using Visual Basic 2010 and Microsoft Access Database, user interface implementation, and system testing. The results of the study indicate that the system built is able to speed up the administration process, minimize data input errors, and produce fast, accurate, and structured reports. The implementation of this system makes it easier for administrative staff to manage patient data, while improving the quality of service at the ATHA Perdagangan Clinic.Keywords: patient administration; visual basic 2010; database access.Â Â Abstrak: Penelitian ini bertujuan untuk merancang dan membangun Sistem Informasi Administrasi Kepasienan berbasis web pada Klinik ATHA Perdagangan guna meningkatkan efektivitas dan efisiensi layanan administrasi pasien. Sistem ini dikembangkan untuk menggantikan proses manual yang selama ini digunakan, seperti pencatatan pasien, pengelolaan data obat, pengaturan data ruang, serta pencatatan transaksi pembayaran rawat inap dan rawat jalan, yang rentan terhadap kesalahan dan memakan waktu. Metode pengembangan sistem meliputi analisis kebutuhan, perancangan sistem menggunakan Visual Basic 2010 dan Database Microsoft Access, implementasi antarmuka pengguna, serta pengujian sistem. Hasil penelitian menunjukkan bahwa sistem yang dibangun mampu mempercepat proses administrasi, meminimalkan kesalahan input data, serta menghasilkan laporan yang cepat, akurat, dan terstruktur. Implementasi sistem ini memberikan kemudahan bagi petugas administrasi dalam mengelola data pasien, sekaligus meningkatkan kualitas pelayanan di Klinik ATHA Perdagangan.Kata Kunci: administrasi pasien; visual basic 2010; database access